“Efecto de la aplicación de cuatro dosis de fertilizante orgánico enriquecido con microorganismos eficientes (ferti em ) en el rendimiento de grano seco del frijol trepador (phaseolus vulgaris) variedad huasca poroto en el distrito de Lamas - Goigochea Pinchi, Diego (2015)
The present research work entitled "Effect of the application of four doses of organic fertilizar enriched with effective microorganisms (EM Ferti) in dry seed yield of climbing bean (Phaseolus vulgaris) variety Huasca Poroto in the district of Lamas" took out in order to evaluate the effect of tour doses of tour doses of organic fertilizar enriched with effective microorganisms (EM Ferti) in dry seed yield of climbing bean variety Huasca Poroto and performing economic analysis of treatments. Statistical Design randomized complete block (RCBD) with three replications and tour treatments was used. The results indicate that the application of 0.8 t I ha-1(T3) of organic matter (Ferti EM) higher average yields, seed weight, number of seeds I pod and number of pods per plant with 7 529.82 kg ha-1, 0.48 g, 8.3 were obtained 168. 7 seeds and pods per plant respectively, statistically beating the averages of the other treatments, followed by T2 (0.6 t ha-1), T4 (1 t ha-1), T1 (0.4 t ha-1) and TO (control). The T3 (0.8 t ha-1) treatment gave the best value of B I C with 3.67 anda net profit of S l. 13691.57 soles, followed by T2 (0.6 t ha-1), T4 (1 t ha-1) and T1 (0.4 t ha-1), who obtained values of B I C of 2.83, 2.08 and 1.37 with net profit of SI .9 465.12; S / 5 014.46; and SI .1 602.60 soles, respectively. The treatments TO (control) received a B I C value 0.71 anda negativa net profit of S l. -1157.35 Soles. Keywords: lndeed, dose, Ferti EM, beans, trellis, analysis, economic, seed pod weight.